2018
DOI: 10.1111/bcpt.13119
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical predictors of Multi‐Walled Carbon Nanotube–induced pulmonary histopathology and toxicity one year after pulmonary deposition of 11 different Multi‐Walled Carbon Nanotubes in mice

Abstract: Multi-walled carbon nanotubes (MWCNT) are widely used nanomaterials that cause pulmonary toxicity upon inhalation. The physicochemical properties of MWCNT vary greatly, which makes general safety evaluation challenging to conduct. Identification of the toxicity-inducing physicochemical properties of MWCNT is therefore of great importance. We have evaluated histological changes in lung tissue 1 year after a single intratracheal instillation of 11 well-characterized MWCNT in female C57BL/6N BomTac mice. Genotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 72 publications
4
53
0
Order By: Relevance
“…One of the main fields of studies on the toxicity of CNTs is an impact on the pulmonary system [165,166]. The CNTs belong to the big group of respirable materials, and they potentially can cause the inflammation of lung tissues.…”
Section: Toxicity Studies Of Carbon Nanotubesmentioning
confidence: 99%
“…One of the main fields of studies on the toxicity of CNTs is an impact on the pulmonary system [165,166]. The CNTs belong to the big group of respirable materials, and they potentially can cause the inflammation of lung tissues.…”
Section: Toxicity Studies Of Carbon Nanotubesmentioning
confidence: 99%
“…Although the mechanism is not clear, several studies suggest that CNT may trigger the activation of the Nlrp3 inflammasome complex in macrophages and other phagocytic cells, resulting in caspase-1-mediated activation and release of pro-inflammatory cytokines 110; 119-121 . The ensuing pulmonary inflammatory response normally results in clearance of the foreign particles, tissue repair, and recovery; however, repeated exposure to a biopersistent CNT like L-MWNT-1020 can result in chronic inflammation and tissue damage 122 .…”
Section: Discussionmentioning
confidence: 99%
“…After pulmonary exposure to MWCTs, a marked inflammatory response was present and associated with the development of granulomas and/or fibrosis [ 49 , 96 ]. Depending on the physicochemical properties of MWCTs, nanomaterial was detected one year later as black aggregates in macrophages or in granuloma [ 97 ]. Yanamala et al showed distinct and common inflammatory responses to various carbonaceous materials, including MWCTs [ 98 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%